Learning lessons from chemical incidents – What’s stopping us and how we can make it happen - Wood, Maureen Heraty; Koutelos, Konstantinos; Hailwood, Mark; Cowley, Charles (Associazione Italiana Di Ingegneria Chimica (AIDIC), 2020)
While the value of lessons learning is proclaimed far and wide by industry experts, recent accidents in OECD countries put into question the degree to which high hazard industries are using accident information effectively. Lessons learning is a central part of chemical accident risk management because it confronts the reality that individuals, and at a larger scale, organisations, can be blind to the potential for failure in a system. The safety management system (SMS) and the risk management processes, which encompass hazard identification, risk assessment and risk treatment, are the expression of conscious efforts to deal with these vulnerabilities. Insufficient identification of hazards in process design, and underestimation of the risk associated with even the smallest deviations from established standards and procedural norms may have serious and sometimes even fatal impacts. So it is crucial that lessons learned from incidents provide input into the risk analysis process. It is equally important that those involved know how to identify and apply the relevant lessons from the resources available and do so. There is plenty of evidence from recent accidents and studies that lessons available from incidents were not used effectively. While there is an ample supply of chemical accident information within large corporations as well as in the public domain, the accessibility and exploitation of these resources has not necessarily grown. The authors argue that one explanation for failing to learn from past lessons stems from a collective failure of all stakeholders to invest in lessons learning beyond reporting chemical accident investigation findings. The authors further argue that a major reason for this is that the traditional ‘command and control’ form of leadership, prevalent in industry, inhibits organisational learning by taking inadequate account of the operational context and failing to achieve an effective balance between control and adaptation. Recent empirical studies underline the importance of this balance of administrative and adaptive practices for organisational learning to be effective, so that lessons from incidents are embedded into operational reality. The authors propose how such a learning culture can be achieved by employing specific adaptive and enabling leadership practices.